2019
DOI: 10.21098/bemp.v22i1.1041
|View full text |Cite
|
Sign up to set email alerts
|

Do Information and Communication Technologies Foster Economic Growth in Indonesia?

Abstract: This paper investigates, using annual data from 1980 to 2014, whether adoption of information and communication technologies (ICT) fosters economic growth in Indonesia. We employ an Autoregressive Distributed Lag cointegration technique on an augmented neoclassical growth model. The empirical results indicate a positive effect of ICT development on economic growth in both the long-run and short-run. The other regressors, such as total factor productivity, human capital, and capital per worker, also positively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 49 publications
(62 reference statements)
5
26
0
Order By: Relevance
“…Indonesia as an emerging economy has also experienced an increase in capital stock over time. This is consistent with the findings of Rath (2019).…”
Section: Variablessupporting
confidence: 93%
See 2 more Smart Citations
“…Indonesia as an emerging economy has also experienced an increase in capital stock over time. This is consistent with the findings of Rath (2019).…”
Section: Variablessupporting
confidence: 93%
“…Hence, the present study adds to the extant literature by addressing these important issues in understanding the remittances-growth nexus in Indonesia. Analysis of a single country provides a deeper understanding of how remittances impact growth with the presence of ICT and FSD (Rath and Hermawan, 2019). To the best of our knowledge, this paper is the first to analyze the role of ICT in financial sector development, remittances, and growth nexus.…”
Section: Ict and Economic Growthmentioning
confidence: 97%
See 1 more Smart Citation
“…test various endogenous growth models for Indonesia within the long and short run. Other authors, such asRachman et al (2015) andRath and Hermawan (2019), examine the role of other forms of technology, namely, information and communication technologies, on economic growth in Indonesia. 3 Health(Qureshi and Mohyuddin, 2006) and education(Lucas, 1988) are considered vital elements for increasing human capital, which is seen as an important determinant of economic development.Data from the World Bank on the Human Capital Index (HCI) or related variables are insufficient for Indonesia.…”
mentioning
confidence: 99%
“…Robust panel data estimation was employed in this study. However, another study conducted on Indonesia over 1980 to 2014 by Rath and Hermawan (2019) showed that there is a positive relationship between ICT development and economic growth both in the longrun and short-run period. Figure 1 depicts the variables which are employed in this study.…”
Section: Past Studiesmentioning
confidence: 97%